Repeat exposure to group A streptococcal M protein exacerbates cardiac damage in a rat model of rheumatic heart disease. (16th November 2016) - Gorton, Davina; Sikder, Suchandan; Williams, Natasha L.; Chilton, Lisa; Rush, Catherine M.; Govan, Brenda L.; Cunningham, Madeleine W.; Ketheesan, Natkunam
Abstract: Rheumatic fever and rheumatic heart disease (RF/RHD) develop following repeated infection with group A streptococci (GAS). We used the Rat Autoimmune Valvulitis (RAV) model of RF/RHD to demonstrate that repetitive booster immunization with GAS-derived recombinant M protein (rM5) resulted in an enhanced anti-cardiac myosin antibody response that may contribute to the breaking of immune tolerance leading to RF/RHD and increased infiltration of heart valves by mononuclear cells. With each boost, more inflammatory cells were observed infiltrating heart tissue which could lead to severe cardiac damage. We also found evidence that both complement and anti-M protein antibodies in serum from rM5-immunized rats have the potential to contribute to inflammation in heart valves by activating cardiac endothelium. More importantly, we have demonstrated by electrocardiography for the first time in the RAV model that elongation of P–R interval follows repetitive boost with rM5. Our observations provide experimental evidence for cardiac alterations following repeated exposure to GAS M protein with immunological and electrophysiological features resembling that seen in humans following recurrent GAS infection.